Pengembangan Media Pembelajaran Augmented Reality Berbasis STEM Berbantuan Assembler Edu Untuk Materi Makan dan Dimakan - Ayuningtyas, Octyara Dwi; Anggoro, Subuh; Fukui, Masanori (Jurnal Ilmiah Global Education, 2025)
This study focuses on the development of a STEM-oriented Augmented Reality (AR) learning medium for the topic “Eating and Being Eaten,” facilitated through the Assemblr Edu platform. It involves assessments of content feasibility, student usability testing at SD Negeri 2 Mersi, and evaluations of teacher feedback. The research follows Thiagarajan’s 4-D model, which comprises the stages of define, design, develop, and disseminate. Data were gathered using questionnaires and interviews, with participants including students, teachers, as well as media and content validators.The data analysis combined descriptive quantitative and qualitative approaches. Validation by content experts yielded a score of 87,53%, indicating a high level of validity. Similarly, media experts assessed the product at 81.25%, also categorized as highly valid. A small-scale trial involving 20 students resulted in a 92.33% score, suggesting strong student interest. Meanwhile, teacher feedback from 51 participants resulted in a 92.44% score, reflecting excellent reception. These findings indicate that the developed media is engaging, positively received, and practically applicable in learning environments.